2019
DOI: 10.1002/14651858.cd009629.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar versus monopolar transurethral resection of the prostate for lower urinary tract symptoms secondary to benign prostatic obstruction

Abstract: Bipolar versus monopolar transurethral resection of the prostate for lower urinary tract symptoms secondary to benign prostatic obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 160 publications
1
14
0
1
Order By: Relevance
“…In a Cochrane review of 59 randomized trials that compared monopolar and bipolar TURP, it was stated that incidence of TURP syndrome is more in monopolar TURP group as compared to bipolar TURP group. 9 Patients who were operated by bipolar TURP stayed in hospital for a mean duration of 2.07 days in compared to patients operated by monopolar TURP which stayed for duration of 3.5 days in hospital. The difference in post op hospital stay is statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…In a Cochrane review of 59 randomized trials that compared monopolar and bipolar TURP, it was stated that incidence of TURP syndrome is more in monopolar TURP group as compared to bipolar TURP group. 9 Patients who were operated by bipolar TURP stayed in hospital for a mean duration of 2.07 days in compared to patients operated by monopolar TURP which stayed for duration of 3.5 days in hospital. The difference in post op hospital stay is statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…10 A recent Cochrane review of 59 randomized controlled trial comparing monopolar TURP to B-TURP, concluded that both currents result in comparable improvement of the urological symptoms; however, B-TURP is associated with lower risk of TUR syndrome and blood transfusion. 11 In this setting, we evaluated the use of B-TURP in the management of prostates more than 100 g in size showing that it is a safe and efficient technology even for large prostates.…”
Section: Discussionmentioning
confidence: 99%
“… Surgery should be offered as a primary modality for patients presenting with complications arising secondary to BPH such as renal insufficiency, refractory urinary retention, recurrent urinary tract infections, recurrent bladder stones, and gross hematuria (GR strong) Surgery shall be offered as an alternative to patients presenting with moderate-to-severe LUTS who failed to respond to medical management and who are not tolerant or compliant to medical management (GR optional) Open prostatectomy shall be offered for treatment of moderate-to-severe LUTS in men with prostate size >80–100 ml if endoscopic enucleation techniques are not available or are deemed unsuitable for the patient[ 23 24 ] (GR selective) Transurethral resection of prostate (TURP) should be offered to treat moderate-to-severe LUTS in men with prostate size 30–80 ml[ 25 ] (GR strong) Transurethral incision of prostate should be offered to treat LUTS in men with prostate size <30 ml, in absence of a median lobe[ 26 ] (GR strong) Bipolar TURP may be offered to treat moderate-to-severe LUTS in men with prostate size 30–80 ml based on equipment availability, surgeon's experience, and patient's choice[ 27 ] (GR optional) Holmium laser enucleation of prostate (HOLEP) should be offered to treat moderate-to-severe LUTS in men as size-independent modality as an alternative to TURP. HOLEP is especially beneficial offered to treat moderate-to-severe LUTS in men with prostate size >80 ml.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Bipolar TURP may be offered to treat moderate-to-severe LUTS in men with prostate size 30–80 ml based on equipment availability, surgeon's experience, and patient's choice[ 27 ] (GR optional)…”
Section: Surgical Treatmentmentioning
confidence: 99%